Growth performance of Holstein calves fed milk or milk replacer with or without calf starter - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2013)
Dissertation (MSc (Agric) : Animal Nutrition)--University of Pretoria, 2008.